Knowledge, Attitude and Nutritional Status in Pregnant Women - Widiastuti, Wiwit; Mutyara, Kuswandewi; Siddiq, Amillia (Althea Medical Journal, 2015)
Background: Nutrition during pregnancy is essential for a healthy pregnancy and childbirth. Malnutritionduring pregnancy may cause a negative impact for both mother and fetus. Pregnant women have to replenishtheir nutritional intake so they have to know nutritional needs for pregnancy. This study aims to evaluatethe association between knowledge towards the attitude and nutritional status among pregnant women inJatinangor Primary Health Care.Methods: This was a cross-sectional study and the subjects were 75 pregnant women selected by consecutiveÂ sampling while they attending Puskesmas Jatinangor for antenatal follow up in October until November2012. Knowledge and attitude was assessed using a questionnaire. The level of knowledge and attitudesÂ were categorized into insufficient, sufficient and good. Nutritional status was assessed by measuring themid upper arm circumference. The level of nutritional status was categorized into good nutritional statusand lower nutritional status.Result: Out of 75 respondents, 24 respondents had good knowledge, 39 respondents had sufficientknowledge and 12 respondents had insufficient knowledge. 15 respondents had good attitude, 51respondents had sufficient attitude, 9 had insufficient attitude. 62 respondents had good nutritional statusand 13 respondents had lower nutritional statusConclusion: Most of subjects have sufficient knowledge and attitude, and majority of the respondents havegood nutritional status. There was significant relationship between knowledge and attitude (p=0.02) andno significant relationship between knowledge and nutrition status (p=0.666). Based on this study, it isexpected to conduct further study about other factors which affect the knowledge, attitude, and practice ofpregnant women to improve the nutritional status.Â [AMJ.2015;2(1):231â4]